2023
DOI: 10.1002/hsr2.1154
|View full text |Cite|
|
Sign up to set email alerts
|

Burden of COVID‐19 disease in Kurdistan province in west of Iran using disability‐adjusted life years

Abstract: Background and Aims: During the coronavirus disease 2019 (COVID-19) pandemic, about seven million people were infected with the disease, of which more than 133,000 died. Health policymakers need to know the extent and magnitude of the disease burden to decide on how much to allocate resources for disease control. The results of this investigation could be helpful in this field.Methods: We used the secondary data released by the Kurdistan University of Medical Sciences between February 2020 to October 2021 to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…In this study, the disease burden was found to be higher compared to studies conducted in Yazd and Kurdistan provinces (18,19) among civilians. This finding shows that the impact of COVID-19 is not the same across the country.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In this study, the disease burden was found to be higher compared to studies conducted in Yazd and Kurdistan provinces (18,19) among civilians. This finding shows that the impact of COVID-19 is not the same across the country.…”
Section: Discussioncontrasting
confidence: 66%
“…Coronavirus disease 2019 (COVID- 19) is an infectious acute respiratory syndrome caused by the novel coronavirus, known as SARS-CoV-2, which serves as the etiological agent. Previous epidemics, such as MERS and SARS-CoV-1, have been documented with comparable etiological origins; however, none have attained the level of significance observed in COVID-19 (1).…”
Section: Introductionmentioning
confidence: 99%